(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
In the era of rapid economic development, corporate governance plays an increasingly important role in the development of enterprises. High-quality accounting information has a profound impact on the company’s internal environment. Corporate governance is the owner’s rectification and improvement of the internal organization of the enterprise, and formulates a solution to its own problems. The improvement of corporate governance requires the specification of accounting information.